2016
DOI: 10.1111/jocn.13228
|View full text |Cite
|
Sign up to set email alerts
|

The Huddling Programme: effects on empowerment, organisational commitment and ego‐resilience in clinical nurses – a randomised trial

Abstract: This study is both significant and relevant to nursing science and practice given that it demonstrated the effectiveness of an empowerment programme in increasing organisational commitment and decreasing actual turnover rates of clinical nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The nurses who belonged to the own will type had a strong sense of pride in the nursing profession, had good control of their mental health, and tended to overcome stress by achieving a balance between work and their personal time with their strong willpower. This is in line with the findings of the previous studies [3,6,13,24]. Gillespie et al [24] revealed that hope, self-efficacy, control, coping, and competence influenced the level of resilience in nurses working in the operating room and reported that selfefficacy and control had a strong correlation with resilience, emphasizing on the importance of willpower in resilience, and Ablett and Jones [13] found that hardiness and coherence were the components of resilience in hospice nurses.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The nurses who belonged to the own will type had a strong sense of pride in the nursing profession, had good control of their mental health, and tended to overcome stress by achieving a balance between work and their personal time with their strong willpower. This is in line with the findings of the previous studies [3,6,13,24]. Gillespie et al [24] revealed that hope, self-efficacy, control, coping, and competence influenced the level of resilience in nurses working in the operating room and reported that selfefficacy and control had a strong correlation with resilience, emphasizing on the importance of willpower in resilience, and Ablett and Jones [13] found that hardiness and coherence were the components of resilience in hospice nurses.…”
Section: Discussionsupporting
confidence: 82%
“…According to a survey by the hospital nurse society, the average turnover rate of nurses was 12.4% in 2015, and the turnover rate of new nurses was only 33.9%, which is more than twice the turnover rate of the whole hospitals [2]. This high turnover rate increases the burden of cost and time required to recruit and educate new staff, and it also creates a burden on the remaining nurses, which can be a factor in the turnover [3]. Many studies have attempted to explore the factors influencing the turnover of nurses including working environment, job stress, low income, organizational culture, shift, workefamily conflict, and personality characteristics [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of the PPIs has been tested in many cultures beyond English-speaking populations. For example, there are PPIs studies in Norway (Drozd, Mork, Nielsen, Raeder, & Bjørkli, 2014), Switzerland (Gander, Proyer, Ruch, & Wyss, 2013), Turkey (Koydemir & Sun-Selisik, 2015), Israel (Gelfin, Zohar, & Lev-Ari, 2018) Iran (Dowlatabadi et al, 2016), Japan (Otake, Shimai, Tanaka-Matsumi, Otsui, & Fredrickson, 2006), China (Lü, Wang, & Liu, 2013), Korea (Im, 2016), Taiwan (Wu & Koo, 2016) or Suriname (Hendricks, 2017). To date there have been some initial research in Greece by Symeonidou, Moraitou, Pezirkianidis, & Stalikas (2018) and Dimitropoulou & Leontopoulou (2017).…”
Section: Introductionmentioning
confidence: 99%